Speciation Analysis of Nickel in the Soils of Tejgaon Industrial Area of Bangladesh (Bangladesh Journal of Scientific and Industrial Research, 2009)
The main focus of the study is Tejgaon industrial area which is located within the Dhaka City Corporation and about 5 km north of the city centre. The industries around the study area like battery, chemical manufacturing, electrical and electronic, metal finishing, mining, paint and dye, textiles, pharmaceuticals, pesticides, etc, discharge heavy metals like Ni with their effluents and wastes. At Tejgaon soil the minimum pH value was 5.3 and the maximum 7.6 (at 26°C). High buffering capacity resulting from high soil organic matter content (4.87-11.55%) probably influenced soil pH. Electrical conductivity (EC) (25-551 μS/cm) and organic matter (OM) (4.87-11.55%) contents were also influenced by the industrial wastes and effluents of the factories. In the wet season, the average Ni concentration in different soil fractions was 1.69, 4.16, 13.21 and 93.12 mg kg-1 in water-soluble, NH4OAc extractable, DTPAextractable and total fractions respectively. Comparing wet season and dry season sampling data, total Ni concentrations in different locations were higher in the dry season and the mean concentration of total Ni was 223.89 mg kg-1, which was more than 4 times higher than the tolerable limit. Concentrations of total Ni in different locations during wet season were found above the natural background level with few exceptions. Ni concentration in the group of tolerable level was 21% (>022-=50 mg kg-1) and 75% (=50 mg kg-1) soil samples were found in the group of in excess of tolerable level during wet season. During dry season, 11% of Ni (=50 mg kg-1) samples were in the normal range and 89% (>50 mg kg-1) soil samples were found in the group of in excess of tolerable level. Ni concentration during dry season samples in different extraction i.e in NH4OAc extractable, DTPA extractable and in total fraction was found to decrease with distance away from the disposal point source due to dilution of the effluent and water. The decreasing tendency with distance indicates the accumulation of metals by the industrial operations. Key words: Speciation,Tejgaon soil, Industrial area, Nickel.     doi: 10.3329/bjsir.v44i1.2717 Bangladesh J. Sci. Ind. Res. 44(1), 87-108, 2009